2020
DOI: 10.1007/s00125-020-05335-w
|View full text |Cite
|
Sign up to set email alerts
|

Human skeletal muscle mitochondrial dynamics in relation to oxidative capacity and insulin sensitivity

Abstract: Aims/hypothesis Mitochondria operate in networks, adapting to external stresses and changes in cellular metabolic demand and are subject to various quality control mechanisms. On the basis of these traits, we here hypothesise that the regulation of mitochondrial networks in skeletal muscle is hampered in humans with compromised oxidative capacity and insulin sensitivity. Methods In a cross-sectional design, we compared four groups of participants (selected from previous studies) ranging in aerobic capacity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…Amongst the vast array of insulin-sensitizing adaptations from chronic exercises, enhanced oxidative capacity is one of the most regarded. Indeed, a high SM mitochondrial density has been relentlessly highlighted as a univocal feature of SM-IS ( Gouspillou et al, 2014 ; Roden and Shulman, 2019 ; Houzelle et al, 2020 ). Conversely, mitochondrial dysfunction has been related to loss of SM mass ( Gouspillou et al, 2010 ) Furthermore, peripheral OXPHOS capacity is positively associated with an efficient glucose metabolism ( Rimbert et al, 2004 ).…”
Section: Narrative Literature Reviewmentioning
confidence: 99%
“…Amongst the vast array of insulin-sensitizing adaptations from chronic exercises, enhanced oxidative capacity is one of the most regarded. Indeed, a high SM mitochondrial density has been relentlessly highlighted as a univocal feature of SM-IS ( Gouspillou et al, 2014 ; Roden and Shulman, 2019 ; Houzelle et al, 2020 ). Conversely, mitochondrial dysfunction has been related to loss of SM mass ( Gouspillou et al, 2010 ) Furthermore, peripheral OXPHOS capacity is positively associated with an efficient glucose metabolism ( Rimbert et al, 2004 ).…”
Section: Narrative Literature Reviewmentioning
confidence: 99%
“…Recent studies have shown that disorder in the balance between mitochondrial fission and fusion is implicated in mitochondrial damage and dysfunction in skeletal muscle in obesity. 43 , 44 We detected a decrease in the mitochondrial fusion protein MFN2 and an increase in the fission protein DRP1 in the genioglossi of HFD-induced obese mice, indicating that obesity impaired mitochondrial fusion and induced excessive mitochondrial fission in the genioglossus. Our in vitro data support this conclusion.…”
Section: Discussionmentioning
confidence: 77%
“…Mitochondrial fission is divided into the fission of membranes and outer membranes in mitochondria and is regulated by DRP1 ( 43 , 44 ). DRP1 is classified as a homologous protein of guanosine triphosphate (GTP) hydrolyzed enzyme (GTPase) power protein.…”
Section: The Physiological State Of Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%